2023
DOI: 10.1186/s13195-022-01121-5
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy is associated with improved cognition and larger brain volumes in at-risk APOE4 women: results from the European Prevention of Alzheimer’s Disease (EPAD) cohort

Abstract: Background The risk of dementia is higher in women than men. The metabolic consequences of estrogen decline during menopause accelerate neuropathology in women. The use of hormone replacement therapy (HRT) in the prevention of cognitive decline has shown conflicting results. Here we investigate the modulating role of APOE genotype and age at HRT initiation on the heterogeneity in cognitive response to HRT. Methods The analysis used baseline data fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 91 publications
0
50
1
Order By: Relevance
“…After long-term HT, we observed a beneficial increase in bone density. Interestingly, HT has been recently associated with improved delayed memory, mitigating the higher life-time risk of Alzheimer disease 26 . Altogether, these results are contrary to the main findings of the WHI study.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…After long-term HT, we observed a beneficial increase in bone density. Interestingly, HT has been recently associated with improved delayed memory, mitigating the higher life-time risk of Alzheimer disease 26 . Altogether, these results are contrary to the main findings of the WHI study.…”
Section: Discussioncontrasting
confidence: 77%
“…Interestingly, HT has been recently associated with improved delayed memory, mitigating the higher life-time risk of Alzheimer disease. 26 Altogether, these results are contrary to the main findings of the WHI study. The administration of conjugated equine estrogen in WHI cohort versus transdermal estradiol in our study may have an impact on these differences.…”
Section: Discussionmentioning
confidence: 59%
“…For example, results of the Phase 3 Lecanemab trial revealed that females and APOE4 homozygotes did not show improved cognition in response to Lecanemab treatment, while males and APOE4 carriers showed significant improvement (66). Additionally, hormone replacement therapy was shown to interact with APOE genotype to yield different efficacies in AD risk prevention in post-menopausal women (67). Since APOE signals through TREM2 (50), the sex biases observed in TREM2 signaling pathways in aged microglia may be contributing to the differential response to AD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition, in women who are APOE4 carriers and therefore at high risk for Alzheimer's disease, early MHT may represent an effective targeted strategy to mitigate their higher lifetime risk of Alzheimer's disease. 63,64 Further investigation in this area is still warranted, as data from the literature are somewhat contradictory. Indeed, recent North European Finnish/Danish case-control studies, based on national registries, have pointed towards a relationship between MHT and the risk of developing Alzheimer's disease and/or late-onset dementia.…”
Section: Cognition and Moodmentioning
confidence: 99%